Anti-inflammatory and antioxidant effects of nanoformulations composed of metal-organic frameworks delivering rutin and/or piperine natural agents. (1st January 2021) - AbouAitah, Khaled; Higazy, Imane M.; Swiderska-Sroda, Anna; Abdelhameed, Reda M.; Gierlotka, Stanislaw; Mohamed, Tarik A.; Szałaj, Urszula; Lojkowski, Witold
Abstract: Plant-derived natural medicines have been extensively studied for anti-inflammatory or antioxidant properties, but challenges to their clinical use include low bioavailability, poor solubility in water, and difficult-to-control release kinetics. Nanomedicine may offer innovative solutions that can enhance the therapeutic activity and control release kinetics of these agents, opening the way to translating them into the clinic. Two agents of particular interest are rutin (Ru), a flavonoid, and piperine (Pip), an alkaloid, which exhibit a range of pharmacological activities that include antioxidant and anti-inflammatory effects. In this work, nanoformulations were developed consisting of two metal–organic frameworks (MOFs) with surface modifications, Ti-MOF and Zr-MOF, each of them loaded with Ru and/or Pip. Both MOFs and nanoformulations were characterized and evaluated in vivo for anti-inflammatory and antioxidant effects. Loadings of ∼17 wt.% for a single pro-drug and ∼27 wt.% for dual loading were achieved. The release patterns for Ru and or Pip followed two stages: a zero-order for the first 12-hour stage, and a second stage of stable sustained release. At pH 7.4, the release patterns best fit to zero-order and Korsmeyer–Peppas kinetic models. The nanoformulations had enhanced anti-inflammatory and antioxidant effects than any of their elements singly, and those with Ru or Pip alone showed stronger effects than those with both agents. Results of assays using a paw edema model, leukocyte migration, and plasma antioxidant capacity were in agreement. Our preliminary findings indicate that nanoformulations with these agents exert better anti-inflammatory and antioxidant effects than the agents in their free form.